DAMPAK DAMPAK OMNIBUS LAW TERHADAP KEWENANGAN PEMERINTAH DAERAH DALAM PENGELOLAAN LINGKUNGAN HIDUP DI INDONESIA: DAMPAK OMNIBUS LAW TERHADAP KEWENANGAN PEMERINTAH DAERAH DALAM PENGELOLAAN LINGKUNGAN HIDUP DI INDONESIA - Khoirotul Hijriah, Nurul; Syam, Fauzi (Mendapo: Journal of Administrative Law, 2024)
This research aims to analyze the impact of the Omnibus law on regional government authority in environmental management in Indonesia. The method used in this research is document analysis and literature study. The research results show that adopting the Omnibus law results in changes in environmental regulations that can lead to the degradation of local government authority. Some authorities previously owned by regional governments in environmental management, such as environmental permits, pollution control, and natural resource management, can be transferred to the central government level. This degradation of local government authority in environmental management has a significant impact. One of them is a lack of responsiveness to specific environmental problems at the local level. Different environmental conditions between regions require different approaches to management. If local governments' authority is limited, their ability to deal with environmental problems effectively will also be limited. Apart from that, the degradation of local government authority can also reduce community participation in decision-making related to the environment. Active and involved community participation in environmental management is crucial for sustainable development. However, if local government authority is limited, community participation may be hampered and local interests may not be well represented.